A convenient synthesis of N-tert-butyl amides by the reaction of di-tert-butyl dicarbonate and nitriles catalyzed by Cu(OTf)2. Issue 9 (September 2020) - Yang, Wanfeng; Feng, Chengliang; Tang, Yuqi; Ji, Min; Chen, Junqing
The utility of Cu(OTf)2 as the catalyst for the synthesis of a series of N - tert -butyl amides in excellent isolated yields via the reaction of nitriles (alkyl, aryl, benzyl, and furyl nitriles) with di- tert -butyl dicarbonate is described. Cu(OTf)2 is a highly stable and efficient catalyst for the present Ritter reaction under solvent-free conditions at room temperature.